Negligible nuclear introgression despite complete mitochondrial capture between two species of chipmunks. (21st July 2015) - Good, Jeffrey M.; Vanderpool, Dan; Keeble, Sara; Bi, Ke
<x xml:space="preserve">Abstract</x> The idea that species boundaries can be semipermeable to gene flow is now widely accepted but the evolutionary importance of introgressive hybridization remains unclear. Here we examine the genomic contribution of gene flow between two hybridizing chipmunk species, Tamias ruficaudus and T. amoenus. Previous studies have shown that ancient hybridization has resulted in complete fixation of introgressed T. ruficaudus mitochondrial DNA (mtDNA) in some populations of T. amoenus, but the extent of nuclear introgression is not known. We used targeted capture to sequence over 10, 500 gene regions from multiple individuals of both species. We found that most of the nuclear genome is sorted between these species and that overall genealogical patterns do not show evidence for introgression. Our analysis rules out all but very minor levels of interspecific gene flow, indicating that introgressive hybridization has had little impact on the overall genetic composition of these species outside of the mitochondrial genome. Given that much of the evidence for introgression in animals has come from mtDNA, our results underscore that unraveling the importance introgressive hybridization during animal speciation will require a genome‐wide perspective that is still absent for many species.